The effect of coming from the common language branch on the formation of thought that turns into a cultural code: the korean language example through south korean tv series - ALGÜL, NEVİN (My University, 2022)
Researching and examining the similarities between the languages connected to the common language branch in the formation stage of the thought that governs human attitudes and attitudes, through cultural codes; One of the side implications of this research, which aims to present the similarities with examples and to bring them to a conclusion, is the issue of whether religion or language is dominant over the comparatively human, attitude and thought that determines his attitude. Therefore, the language-thought-religion triangle will be discussed especially in the results section.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Language Family; Common Language Branch; Body Language; Confucius; Korean Language; Religion; Thought Formation